Studi Eksperimental Pengaruh Variasi Jumlah Blade pada Turbin Angin Archimedes Spiral - Darwin Harun; Muhammad Ilham Maulana; Riza Mirza (Jurnal Teknik Mesin Unsyiah, 2018)
Wind energy is one of the energy that is starting to be used to produce electricity or convert it to mechanical energy for other purposes. One of the tools used to harness wind energy is a wind turbine. Indonesia, especially Aceh, is one of the countries that has not used wind energy as a power plant because of the characteristics of wind in Indonesia which tends to be low-speed. Archimedes spiral wind turbine is a new type of wind turbine that can operate at low wind speeds, consisting of two to three Circular blades form an axis, then wrapped around each other and one side is extended, the design of this turbine essentially mimics the shell of the Nautilus snail (Biomimicry). The basic principle of this wind turbine is designed using the legal principle of Archimedes. This scientific work will analyze the effect of variations in the number of blades on rotation and the influence of blade rotation on wind speed using the experimental method, therefore turbines are made with variations of 2 blades and 3 blades, and the outer diameter is 80 cm and overall length is 90 cm. From the results of the study it was found that the 3 blade wind turbine has a better percentage of shaft rotation compared to the 2 blade wind turbine that is equal to 16.67%. Maximum wind power occurs on the 4th floor with a value of 164.3 watts